REVIEW: Cyberspace, kavabowls and hot news in the Pacific - David Robie (Asia Pacific Network, 1996)
Review of Tahiti Pacifique, Tahiti Beach Press, The National, Post-Courier, Samoa Observer, Tonga Chronicle, Matangi Tonga, Uni Tavur, Papua Niugina Nius, Online Journalist's 'Tonga Page', CocoNet Wireless, Pacific Islands Internet services, Cafe Pacific, Rabi Online.